EFFECT OF TRAINING PROGRAMMES ON KNOWLEDGE LEVELS OF PADDY AND COTTON FARMERS IN PRAKASAM DISTRICT OF ANDHRA PRADESH - SARADA, O. (The Journal of Research, PJTSAU, 2019)
To assess the effect of the training programmes organized by District Agricultural Advisory and Transfer of Technology Centre (DAATTC), Ongole, an investigation was carried out in Prakasam district of Andhra Pradesh during the year 2016-17. Training programmes organized for thirty paddy farmers and thirty two cotton farmers and the trainees of the training programme were the sample for the study purpose. The effectiveness of the training programme was assessed by studying knowledge levels of the farmers before and after participating in training programmes. Majority of the paddy farmers were in middle age group,with high school education, medium farming experience, farm size, extension contact, innovativeness, trainings undergone and mass media exposure. Sixty per cent of the paddy farmers were with low knowledge in pre test followed by one third with medium and almost seven per cent with high knowledge. With respect to post knowledge test fifty three per cent of the paddy farmers were in high knowledge group followed by forty per cent in medium and almost seven per cent with low knowledge. Regarding knowledge gain of the farmers sixty per cent were with high knowledge gain followed by medium (30.00%) and low (10.00%)categories. Majority of the cotton farmers were in middle age group, functionally literate and with high farming experience, medium and low farm size, medium extension contact, innovativeness, trainings undergone and mass media exposure Forty seven per cent (46.88%) of the cotton farmers were with low knowledge followed by 43.75 per cent in medium and 9.37 per cent in high knowledge groups in pre test. Whereas fifty six per cent of the farmers were with medium knowledge followed by high (40.63%) and low (3.13%) knowledge groups in post knowledge test. Almost half the cotton farmers were found with high knowledge gain followed by medium (40.63%) and low (12.50%) categories. Education, mass media use, extension contact and trainings undergone by the paddy farmers were found to have significant positive relation with their knowledge gain. Extension contact, innovativeness,mass media use and trainings undergone had significant positive relation with their knowledge gain with respect to cotton farmers.